Driver Safety High Cabin and Chassis Design in Diesel Forklifts - Ã‡ETÄ°N, Halil (International Journal of Computing and Engineering, 2023)
Purpose: In general, most forklift accidents occur due to rollover. After a rollover, the first affected part is the driver's cabin, followed by the chassis and parts. In the study, cabin and chassis designs of diesel forklifts with increased driver safety and performance were made. Methodology: Cabin and chassis tests were carried out with the Solid works program. According to the test results, the chassis and cabin design was made. Welding and assembly processes on the chassis of high-strength materials suitable for this design have been completed. Findings: As a result of the studies, the cabin design, which is different from other similar forklifts, notches on the edges of the fender, the removal of fuel and oil tanks from the chassis, eliminating the leakage test, and the steps on the sides of the chassis being made monolithic, are important innovations. Unique contributor to theory, policy and practice: As a result of all these studies, our KFD30 model was developed. This new model stands out with its new design and manufacturing on the forklift.